The Impact Of Human Resource Management Practices On Organizational Commitment: Organizational Justice As Mediator Among Academic Staff Of Public Universities In Malaysia - Sukaina Shaban Tarban
This study examined the relationships between the four dimensions of human resource management practices and the three dimensions of organizational commitment among academic staff in higher education in Malaysia. The dimensions of organisational commitment as operationalised by this study are affective commitment, continuance commitment, and normative commitment. Human resource management practices also as operationalised by this study are good and safe working conditions, recruitment and selection, equal employment opportunities, and training and development. Furthermore, this study also investigated the mediating effects of organisational justice on the relationships between human resource management practices and organisational commitment among academic staff in higher education in Malaysia. Data were collected from three Malaysian public universities among 496 respondents using a Likert Scale survey instrument. Data analysis was conducted using Structural Equation Modelling (SEM) techniques via AMOS 20 and SPSS 20 for testing the study hypotheses. This research contributes to HRM literature particularly in the area of HRMPs and OC relationships via OJ as mediator among academics’ staff in public universities in Malaysia, which have not been examined previously. The results obtained indicated that for the majority of the hypothesised relationships two out of three direct relationships were supported, and one direct relationship was not supported. The result of the mediator test hypothesis was significant. The outcome of this study provides very sound insight into the study of organisational commitment in the public sector, particularly in higher education in Malaysia. It will also benefit the government, policymakers, and other concerned agencies in Malaysia. Organisational justice has been proven by this study as a strategic tool that could be efficiently used by managers to effectively manage the commitment of their staff. This research encountered limitations such as the inability to include other Malaysian public universities and instead focusing on only three universities.